What Are the bona fide GSK3 Substrates?. (18th May 2011) - Sutherland, Calum
Abstract : Nearly 100 proteins are proposed to be substrates for GSK3, suggesting that this enzyme is a fundamental regulator of almost every process in the cell, in every tissue in the body. However, it is not certain how many of these proposed substrates are regulated by GSK3 in vivo . Clearly, the identification of the physiological functions of GSK3 will be greatly aided by the identification of its bona fide substrates, and the development of GSK3 as a therapeutic target will be highly influenced by this range of actions, hence the need to accurately establish true GSK3 substrates in cells. In this paper the evidence that proposed GSK3 substrates are likely to be physiological targets is assessed, highlighting the key cellular processes that could be modulated by GSK3 activity and inhibition.